Surface relations : queer forms of Asian American inscrutability - Huang, Vivian L., 1986- (Duke University Press, 2022)
"In Surface Relations Vivian L. Huang traces how Asian and Asian American artists have strategically reworked the pernicious stereotype of inscrutability as a dynamic antiracist, feminist, and queer form of resistance. Following inscrutability in literature, visual culture, and performance art since 1965, Huang articulates how Asian American artists take up aesthetics of Asian inscrutability-such as invisibility, silence, unreliability, flatness, and withholding-to express Asian American life. Through analyses of diverse works by performance artists (Tehching Hsieh, Baseera Khan, Emma Sulkowicz, Tseng Kwong Chi), writers (Kim Fu, Kai Cheng Thom, Monique Truong), and video, multimedia, and conceptual artists (Laurel Nakadate, Yoko Ono, Mika Tajima), Huang challenges neoliberal narratives of assimilation that erase Asianness. By using sound, touch, and affect, these artists and writers create new frameworks for affirming Asianness as a source of political and social critique and innovative forms of life and creativity."--